The interim experts’ counsil resolution on the EMPA-REG OUTCOME trial issues - Editorial team Diabetes Mellitus (Endocrinology Research Centre, 2016)
The interdisciplinary interim experts’ counsil on March 3, 2016 in Moscow have considered the EMPA-REG OUTCOME trial results and suggested a number of prorositions and remommendations on further empagliflozin’s cardiovascular effects investigation and it’s clinical application in patients with type 2 diabetes at high cardiovascular risk.